BASELINE LEUKOCYTE COUNT AND ACUTE CORONARY SYNDROME: PREDICTOR OF ADVERSE CARDIAC EVENTS, LONG AND SHORT TERM MORTALITY AND ASSOCIATION WITH TRADITIONAL RISK FACTORS, CARDIAC BIOMARKERS AND CREACTIVE PROTEIN - Munir, Tahir Ahmad; Afzal, M Nasir; Rehman, Habib -ur- (Journal of Ayub Medical College Abbottabad, 2009)
Background: The elevated WBC count has been accepted as part of healing response following myocardial infarction as well as a predictor of adverse cardiovascular events. The study was designed to find out correlation between WBC count and coronary risk factors, cardiac biomarkers, C-reactive protein (CRP), incidence of adverse cardiac events and mortality in patients of ACS in Pakistan. Methods: One hundred and thirty-three patients of ACS were stratified according to WBC categories, WBC1 (<7000/mm3), WBC2 (7100-10,000/mm3) and WBC3 (>10,000/mm3). The WBCs were counted on admission by Sysmex cell counter, CRP by immunoturbidimetric method, and CK-MB and Trop-I by enzyme immunoassay. Adverse cardiac events and mortality were recorded for 12 months of follow up period. Results: Long term mortality in patients with ACS was 6.4% in WBC1, 18.2% in WBC2 and 40.9% in WBC3 categories, while short term mortality was 2.6%, 3.0% and 18.2% in WBC1, WBC2, and WBC3 categories respectively. Relative to patients in lower 2 WBC categories, patients in the highest category were 7 times more likely to die during 30 days (HR 7.83, p=0.017) and more than 9 times during the total follow up period (HR 9.42, p<0.001). Cox regression analysis showed WBC3 a strong independent predictor of mortality (HR 6.36, p=0.016). WBC count showed a positive correlation with coronary risk factors, cardiac biomarkers and CRP. Conclusion: WBC count is a strong independent predictor of mortality in patients with ACS and has positive correlation with coronary risk factors, cardiac biomarkers and CRP. Keywords: Acute coronary syndrome, WBCs, Mortality, C-reactive protein